Binding of β-carotene to whey proteins: Multi-spectroscopic techniques and docking studies. (30th March 2019) - Allahdad, Zahra; Varidi, Mehdi; Zadmard, Reza; Saboury, Ali Akbar; Haertlé, Thomas
Highlights: β-Carotene binding to whey proteins contributed to tryptophan quenching. Hydrophobic interactions were the main forces involved in the interaction. β-Lactoglobulin showed the highest binding affinity toward β-carotene. β-Carotene binding affected whey proteins secondary and tertiary structures. Abstract: The objective of this work was to study molecular binding between β-carotene (β-C) and whey protein isolate (WPI) as a function of pH (4–9), temperature (15, 25, and 35 °C), and NaCl concentration (0–0.25 M) using spectroscopic techniques and docking studies. The fluorescence quenching data showed that binding affinity increased with pH, temperature and ionic strength. The binding was entropy driven and involved mostly hydrophobic interactions. Three major whey proteins including β-lactoglobulin (β-Lg), α-lactalbumin (α-Lac), and bovine serum albumin (BSA) were bound to β-C with overall binding constant values of 1.31 × 10 7, 1.80 × 10 4, and 4.51 × 10 4  M −1, respectively. A single class of binding sites for β-C on whey fractions was recognized using Job's method. Docking results revealed β-C was bound to the subdomain IIA of BSA, the residues of aromatic cluster II in α-lactalbumin and into the calyx of β-lactoglobulin resulting in conformational changes in the secondary and tertiary structures of proteins.